(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
Today, the perfect mastery of modern science and high technologies is becoming a decisive condition for the development of any state and society. Therefore, this article presents the ideas that it is extremely important to educate artistic taste in young people, and it is important to form and instill in a person not only a taste for art, but also a taste for life itself.